Hybrid photothermal structure based on Cr-MgF2 solar absorber/PMMA-graphene heat reservoir for enhanced thermoelectric power generation - Kwak, Geonho; Jeong, Yoo Seok; Kim, Sun Woo; Kim, Jin Kyeom; Choi, Jihyeok; Song, Kyung Guen; Kim, Hee Jun; Choi, Won Jun; Yang, Ya; Song, Hyun Cheol; Baik, Jeong Min; Yu, Hak Ki (Nano Energy, 2023)
In this paper, a facile strategy for a hybrid photothermal structure that can efficiently manage solar heat is reported. The hybrid photothermal structure consists of a Cr/MgF2 multilayer structure absorber and a poly(methyl methacrylate) (PMMA)-graphene heat reservoir that prevents the absorbed heat from being lost through radiation or convection. It exhibits a quite high light absorption of approximately 80% over a wavelength range of 0.5–2.5 µm. The thermal conductivity and thermal diffusivity are improved by about 47% according to the addition of graphene to PMMA, effectively transferring the stored heat to a place where it can be used efficiently. When the hybrid photothermal structure was applied to the hot zone of a thermoelectric generator, the output voltage is improved by 2.74 times compared to the device with only the light absorber. In addition, the difference between the high and low temperatures reached up to approximately 27 K.
Keywords: Heat reservoirs; Light absorbers; Low emissivities; Photo-thermal; Photothermal properties; Poly(methyl methacrylate); Poly-methyl methacrylates; Power- generations; Structure-based; Thermoelectric generators; Heat reservoir; Light absorber; Low emissivity; Photothermal properties; Thermoelectric generator